2005
DOI: 10.1021/om050361t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding in a Disilazane Ruthenium Complex. Catalytic Selective Deuteration of Disilazane

Abstract: The disilazane complex [RuH 2 {(η 2 -HSiMe 2 ) 2 -NH}(PCy 3 ) 2 ] (2) was formed by the reaction of the bis-(dihydrogen) complex RuH 2 (H 2 ) 2 (PCy 3 ) 2 ( 1) with 1,1,3,3tetramethyldisilazane. The coordination of the disilazane ligand is discussed on the basis of NMR, X-ray, and DFT studies. The choice of the functional (B3PW91 versus B3LYP) is crucial in this system. 1 is an active catalyst for the selective deuteration of the starting disilazane (HSiMe 2 ) 2 NH into (DSiMe 2 ) 2 NH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 13 publications
(25 reference statements)
2
51
1
2
Order By: Relevance
“…Indeed, we have recently characterized both by X-ray diffraction and DFT calculations the disilazane complex [RuH 2 {(η 2 -HSiMe 2 ) 2 -NH}(PCy 3 ) 2 ] (6). [20] For the first time the choice of the functional for DFT calculations in silane ruthenium chemistry turned to be crucial. Major differences were observed with the use of B3LYP by comparison to the X-ray data, whereas a very good match was obtained with B3PW91 ( Figure 4).…”
Section: Disilane Coordinationmentioning
confidence: 99%
“…Indeed, we have recently characterized both by X-ray diffraction and DFT calculations the disilazane complex [RuH 2 {(η 2 -HSiMe 2 ) 2 -NH}(PCy 3 ) 2 ] (6). [20] For the first time the choice of the functional for DFT calculations in silane ruthenium chemistry turned to be crucial. Major differences were observed with the use of B3LYP by comparison to the X-ray data, whereas a very good match was obtained with B3PW91 ( Figure 4).…”
Section: Disilane Coordinationmentioning
confidence: 99%
“…208 The corresponding disilazane complex was a different structural type with the disilyl groups as well as the two phosphines and the two hydrides each cis to each other (an approximate C 2V disposition for the core P 2 RuSi 2 ). 212 The similarity of the VTNMR data for the disilazane-and disiloxane-derived complexes suggested that the same structure for both derivatives could be assumed. 208 Additional NMR experiments and a more extensive discussion of the possible exchange mechanisms for RuH 2 [{(η 2 -HSiMe 2 ) 2 }(CH 2 ) 2 ](PCy 3 ) 2 have been published, 398 and selected results and conclusions are summarized first for this complex as a prototype for the complexes with this structure and secondly for the two systems with the C 2V disposition for the core P 2 RuSi 2 ligands.…”
Section: H a [Tm](σ-h B -Si) H H B [Tm]m(σ-h A -Si)mentioning
confidence: 91%
“…208,209,212,398 These complexes have two Ru-(η 2 -H-Si) bonds where the silicon centers are also linked together (indicated by X in the general formula). The studies reported spectroscopic properties, various NMR experiments, structural data for selected examples, and calculations, which also included comments on the appropriateness of calculation methods.…”
Section: H a [Tm](σ-h B -Si) H H B [Tm]m(σ-h A -Si)mentioning
confidence: 99%
“…For the complexes [Ru(H) 2 {(h 2 -H-SiMe 2 )X(h 2 -H-SiMe 2 )}(PCy 3 ) 2 ] (with X = O, NH) the barriers are much lower and two stages of decoalescence are observed at much lower temperatures leading to inequivalence of all four hydrogen atoms. [66,67] Nevertheless, the principles of the mechanism are the same.…”
Section: [Mhmentioning
confidence: 99%